Ordboksanvändning hos blivande språkexperter och hos professionella översättare - Pilke, Nina (LexicoNordica, 2008)
The aim of this pilot study is to explore how informants at different professional levels use dictionaries (Swedish/Finnish) and to investigate their opinions on the functionality of different kinds of dictionaries (electronic/book). The study is part of a research project focusing the use and contents of dictionaries by three groups of informants, namely two groups of university students (subject studies / Bachelor’s degree and advanced level studies / Master’s degree) and professional translators in Finland. Both the students and teachers represent the University Vaasa (Faculty of Humanities, Department of Scandinavian Languages) and the translators work in the Vaasa area. The material of the study comprises questionnaires. The discussion in the article is based on the concept of usability, especially the aspect of user acceptability.